ISpring-based instruction media that accommodate student’s learning style to support differentiated instruction - Mardiana, Mardiana; Sukmawati, R Ati; Juhairiah, Juhairiah (Math Didactic: Jurnal Pendidikan Matematika, 2024)
Kurikulum merdeka demands teachers to apply differentiated instruction in the classroom. Differentiated instruction can be applied in four ways, one of them is differentiate content. Differentiate content is done by adjusting how the material will be taught or learned by students based on their learning style. To do this, teachers can present interactive instructional media that accommodate the learning styles of students. Then to present these media, an adequate technology such as iSpring is required. This reseach aims to develop instructional media that accommodates students' learning styles to support differentiated instruction.in trigonometric ratios material using iSpring. The reseach employed R&D method and ADDIE development model. The research was conducted in X RPL 2 SMKN 4 Banjarmasin, which consisted of 36 students with dominant visual and auditory learning styles. The research findings showed that the instructional media developed were valid and very practical for visual students and auditory students.